Significant changes in occupations among college students: a study carried out on a correlated online social network profile (RECIIS, 2024)
This study examines changes in occupational performance as observed in posts by university students on a social network. Depression is prevalent in Brazil, particularly among students, impacting academic and daily functioning. Using CrowdTangle, anonymous Facebook posts were analyzed following American Occupational Therapy Association guidelines. 301 posts revealed occupational changes across seven areas defined by the association. Depressive symptoms hinder academic performance, exacerbating symptoms. Academic stress, loneliness, stigma, loss of leisure interest, and socioeconomic factors contribute to distress. Social engagement and support benefit mental health, while time constraints detrimentally affect academics, especially disadvantaged students. The study underscores the link between occupational changes, academic decline, and depression, proposing six relevant subcategories within the Education domain.